REKONSTRUKSI KOMUNIKASI BUDAYA DALAM KAJIAN LINGUISTIK - Nazar, Muhammad (At-Tabayyuun: Journal Islamic Studies, 2022)
Various people who study historical linguistics may have their own reasons against this field. Anyone can enjoy the intellectual challenge by applying the technique is difficult to 'dig' the past and find out about things that we cannot know about otherwise. There are probably looking for features of the language of 'universal' and how language changes, in an effort to determine what makes us 'human' to be unique (assuming, in fact, that we are very different from other animals). And others may learn the historical linguistic studies in an effort to use information that can tell us about non-linguistic history of the people who use the language. In the last chapter, I will show you the kinds of linguistic history information that can tell us about the history of non-linguistic communities, and how this information is reliable.You have seen that by comparing the number of languages ​​which have certain similarities, it is possible to reconstruct the proto-language ancestors of that language. If we consider the system involves the culture of the facts related to each other, in the same way the language is a system of interrelated facts, it is logically possible to reconstruct the proto-culture in the same way as we reconstruct proto-languages.Clearly, any cultural reconstruction method based on comparative cultivation methods like this will not produce results with the same probability level as we are able to make the reconstruction of phonology, as we approach should involve methods that are not so good, we have to reconstruct the grammar or semantics. In fact, the actual units of a cultural system and the exact nature of the relationship between these units may be more difficult to determine from the reciprocal unit in the grammar and semantics. (Anthropologists have long been envious of the techniques have been developed by linguists to describe a scientific language, and have tried to copy it to describe the culture.) Range 'possibility' of cultural change is more difficult to determine from a variety of possible changes in the grammar and semantics, which again makes it more difficult cultural reconstruction. So, while the reconstruction of culture through the adaptation of the comparative method might be expected, any conclusions we reach in this way should be considered as something that is uncertain.